Relationship between Preventive Behaviors and Knowledge Regarding Cardiovascular Diseases - M Imanipour; Sh Bassampour; H Haghani (Tehran University of Medical Sciences, 2008)
Background & Aim: Modification of unhealthy life style is a preventive method in cardiovascular diseases. It seems that education which results in enhancing knowledge would improve the life style. For developing effective educational plans, it is required to evaluate the knowledge and performance of the patients. So, this study aimed to determine the relationship between the teachers;apos preventive behaviors and their knowledge on cardiovascular risk factors.   Methods & Materials: This cross-sectional study was conducted in five zones of Ministry of Education in Tehran. Seven hundred and three teachers participated in the study. Multi-stage sampling was used to gather data using a self-report questionnaire consisted of demographic characteristics, risk factors of CAD, and related modifiable behaviors. Data were analyzed using Pearson coefficient test to determine correlations. Results: The results showed that the majority of participants (67%) had good knowledge on cardiovascular risk factors with the mean scores of 15.20±2.63 out of 20. Stress was found to be the most recognized risk factor (95.3%). Knowledge about diabetes (61.2%) and gender (17.6%) were in the lowest level. Regarding prevention, just 27.7% of the participants reported healthy nutrition. Some of the patients (35.6%) exercised regularly and majority of them (77.7%) were not active or passive smokers. Pearson coefficient did not find any significant relationship between knowledge level and preventive behaviors among teachers. Conclusion: According to our findings, teachers;apos knowledge level on cardiovascular risk factors was good but it did not result in healthy practice. Therefore, providing effective educational programs about healthy life style can improve their daily life practices, as well as it can affect the knowledge and practice of their students about prevention of CAD.